Spatial analysis of primary healthcare services utilization among women in Cross River State, Nigeria - Peter-Kio, Opirite Boma; Okem, Fred Igbang (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
This study carried out a spatial analysis of primary healthcare services utilization among women of childbearing age in Cross Rivers State. A comparative research design was adopted with a population which consisted of 1,015,300 women in the Northern Senatorial District of Cross Rivers State. A sample size of 880 was selected using the multi-stage sampling procedure. Data was collected using a structured questionnaire with a reliability coefficient of 0.76. Analysis was done using mean and t-test at 0.05 level of significance. The result showed that, primary healthcare services which included: health education concerning prevailing health problems (3.29±0.86 vs 2.64±1.14), prevention and control of common diseases services (3.02±0.99 vs 2.57±1.19), essential drugs (3.04±1.03 vs 2.42±1.18), and adequate supply of safe water and basic sanitation (3.31±0.93 vs 2.43±1.24) were utilized more in urban areas than in rural areas. Based on the findings of the study, it was concluded that women in urban areas are more concerned about their health than those in rural areas. It was recommended among others that stakeholders should adopt a multidimensional approach for more effective coordination and supervision of PHC services particularly disease prevention and adequate provision of essential drugs.